A Review and Comprehensive Study on DC-DC Converters - Anusha, Dharavath; P., Srinivasan; K., Narender R. (Recent Advances in Electrical & Electronic Engineering, 2024)
Background: DC-DC converters are used in various applications based on their required voltage capabilities ranging from milli volts to thousands of volts. Methods: This review paper discusses various voltage boosting techniques, such as buck-boost, switched inductor, switched capacitors, isolated converters, etc., and provides a detailed evaluation of the literature and comparison of different DC-DC converters. Results: This study reports a number of storage elements included, such as inductors and capacitors as well as switches and diodes. Their features along with methodologies, merits, complexity, efficiency, and voltage gain have been tabulated. A comprehensive study, converter classification based on the characteristics, and a detailed analysis of isolated and non-isolated DC-DC converters have also been provided. Conclusion: As this study provides a comparison of each isolated and non-isolated converter's comprehensive gain, this research may help in future topology optimization for the choice of the ideal converter for applications. In addition, the examination of each isolated and non-isolated converter's comprehensive gain comparison has also been presented in this paper.
Keywords: non-isolated converters